Suppression of autumnal sexual morph production in spring by a seasonal timer in an aphid. (20th May 2020) - Matsuda, Naoki; Kanbe, Takashi; Endo, Jun; Akimoto, Shin‐Ichi; Numata, Hideharu
Abstract: Photoperiod is the major seasonal cue for phenotypic plasticity in the regulation of development and reproduction. Aphids have a peculiar mechanism in which sensitivity to the photoperiod is lost for a few months through successive generations after hatching from diapause eggs, and therefore, the mechanism responsible for the photorefractory period is termed "a seasonal timer". However, whether the seasonal timer has adaptive significance has never been investigated. Here, we show that the photorefractory generation avoids an unseasonal sexual morph production under short days in spring in the pea aphid, Acyrthosiphon pisum (Harris). When the seasonal timer operated, the overwintered generation, stem mothers, produced only parthenogenetic progenies under natural photoperiods and temperatures in both warm and cold springs. After repeated parthenogenesis following diapause, however, aphids with an expired seasonal timer produced sexual females and males typical of autumn under natural photoperiods and temperatures in a warm spring. These sexual morphs are thought to have a reproductive disadvantage compared to parthenogenetic morphs in the following summer. We thus conclude that the seasonal timer is adaptive for avoiding sexual morph production in spring. The present study shows, for the first time, that a photorefractory period lasting over generations is a trait of ecological importance. Abstract : Acyrthosiphon pisum produce sexual morphs in warm spring if they lack the function of the seasonal timer. The seasonal timer prevents A. pisum from producing sexual morphs that have a reproductive disadvantage in the following summer. In cold spring, A. pisum do not produce sexual morphs even if the seasonal timer does not function because of long day length at that time.